A randomized, adaptive design, double-blind, 3-arm, parallel study assessing the pharmacokinetics and safety of AVT02, a high-concentration (100 mg/mL) Adalimumab biosimilar, in healthy adult subjects (ALVOPAD FIRST). (2nd September 2022) - Wynne, Christopher; Schwabe, Christian; Lemech, Charlotte; Stroissnig, Heimo; Dias, Roshan; Sobierska, Joanna; Guenzi, Eric; Otto, Hendrik; Sattar, Abid; Kay, Richard; Haliduola, Halimu N.; Berti, Fausto
ABSTRACT: Background: This study (ALVOPAD FIRST) assessed bioequivalence, safety, and immunogenicity of AVT02, an adalimumab biosimilar, compared with reference product adalimumab (EU- and US-approved Humira®). Methods: Healthy subjects (N = 392) were randomized 1:1:1 to receive one 40 mg dose of AVT02, EU-reference product, or US-reference product subcutaneously. An interim analysis was planned when 30 subjects per arm had completed the study, to optimize final sample size. The primary PK parameters were Cmax, AUC0-t, and AUC0-inf . Bioequivalence was demonstrated if the 90% confidence intervals (CI) for the ratio of geometric means for the primary pharmacokinetic (PK) parameters were all contained within the prespecified margins of 80% and 125%. Safety and immunogenicity were assessed until Day 64. Results: The 90% CI for the ratio of geometric means for the primary PK parameters, based on Fisher's Combination test analysis, were all contained within the prespecified bioequivalence margins of 80% and 125%, supporting the demonstration of bioequivalence between AVT02 and both EU- and US-reference product. The safety and immunogenicity profiles were comparable across all three treatment arms. Conclusion: PK bioequivalence was supported between AVT02, US-licensed- and EU-approved-reference product adalimumab. Similar safety and immunogenicity were also demonstrated. Trial Registration: The trial is registered at ClinicalTrials.gov (CT.gov identifier: NCT03849313).